Uma segunda identidade : editorial - Queiroz, João Paulo, 1966- (2019)
This text is based on the theme of identity, and it puts into question the dysphoric duplicity between the identical and the different, in several areas of knowledge. To have a difference one needs an identical as a reference. That is an opposite to what is different, recalling the established opposition between Darwin’s “generic characters” and “specific characters.” Taking discourses as a parallel to species, the text discusses similarities. The topics for discussion are pointed out in each of the articles published in “Estúdio 13.” This ends up with the suspicion that the sense of oneself is to be found in what oneself is not: in the other